Perceptions of TB-HIV comorbidity among the Nomads in Adamawa State, Nigeria - Suraj Abdulkarim; Stephen John; Tomon Garba; Hunpiya Basason; Paul Balogun; Joseph Kuye (BMC, 2024)
Abstract The recalcitrance of Mycobacterium tuberculosis (MTB) to eradication was related to achieving a nonreplicating (dormant) state and the increasing global burden of HIV coinfection. Consequently, understanding the knowledge and perception of the population at risk of tuberculosis-HIV infection is essential to designing a strategy of intervention embraced by the target population. A cross-sectional study was conducted among Nomads in Adamawa State, Nigeria. A multistage sampling technique was employed to recruit consented participants. Self-administered questionnaires were used to gather the required information from 4 nomadic schoolteachers in each selected school. Data were entered into a Microsoft Excel sheet where trends and tables of collated data were developed. The findings show that only 13.5% of the participants expressed the correct perceptions of the complementary relationship between HIV and TB. More people in government employment (35%) understand the coexisting relationship of TB-HIV infections. At the same time, cattle herders and crop farmers who practice the prevalent occupation lack knowledge of TB-HIV relatedness. Across gender, only a proportion of males (14.8%) than females (10.5%) were more likely to show an understanding of the complementary association of HIV and TB, and this difference showed statistical significance (p = 0.0001). In conclusion, male gender, education at a degree or professional level, and employment with the government are factors associated with positive perceptions of TB/HIV relatedness. Thus, there is a need to intensify communication to educate Nomads on HIV and TB-related issues.